1989
DOI: 10.1073/pnas.86.4.1401
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminovascular fibers increase blood flow in cortical gray matter by axon reflex-like mechanisms during acute severe hypertension or seizures.

Abstract: Cerebral blood flow was measured and compared in 10 symmetrical brain regions following unilateral trigeminal ganglionectomy (n = 13), sham operation (n = 6), or trigeminal root section (rhizotomy) (n = 8) in cats. Multiple determinations were obtained in anesthetized and paralyzed animals using radiolabeled mict-ospheres during (i) normocapnia-normotension, (ii) hypercappia (5% C02/95% room air), A third major pathway was recently defined innervating cerebral blood vessels (7). Perivascular sensory axons proj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
1

Year Published

1989
1989
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(41 citation statements)
references
References 37 publications
3
37
0
1
Order By: Relevance
“…In all groups studied, regional CBF was symmet rical under resting conditions, and values were sim ilar to those previously reported by our group (Moskowitz et al, 1989a;Sakas et al, 1989). CBF was symmetrical in all brain regions in the three animals in which microspheres with five different isotopic labels were injected to validate the meth odology.…”
Section: Cbf: Intact Animalssupporting
confidence: 87%
See 1 more Smart Citation
“…In all groups studied, regional CBF was symmet rical under resting conditions, and values were sim ilar to those previously reported by our group (Moskowitz et al, 1989a;Sakas et al, 1989). CBF was symmetrical in all brain regions in the three animals in which microspheres with five different isotopic labels were injected to validate the meth odology.…”
Section: Cbf: Intact Animalssupporting
confidence: 87%
“…Recent reports from our laboratory have shown that trigeminal neurogenic mechanisms are in part responsible for the phase of acute hyperperfusion (Moskowitz et al, 1989a;Sakas et al, 1989). Trigeminovascular sensory afferent nerves are largely unmyelinated C fibers surrounding cerebral arteries, arterioles, and veins.…”
mentioning
confidence: 99%
“…Following unilateral removal of the TG, the blood flow increases induced by severe hypertension or seizures were 25% lower on the lesioned than on the unlesioned side when measured using radiolabeled microspheres. 21 Recent data suggest that these increases in blood flow are mediated by local axonal mechanisms and do not involve central transmission. Dual (sensory, motor) function of peri vascular afferents suggest a complex role for tachykinin and other neuropeptide-containing sensory fibers in the physiology of the cerebrovasculature.…”
Section: Discussionmentioning
confidence: 99%
“…of either sex and weighing 2.2-5.2 kg, were used for all experiments. Chronic left trigeminal ganglionectomy was per formed in 8 animals [5][6][7],…”
Section: Methodsmentioning
confidence: 99%
“…The generation of vasoactive metabolites during ischemia, such as lactic acid, adeno sine and free oxygen radicals, contribute to postocclusive hyperemia [3,4], Recent re ports from our laboratory have demon strated the importance of axon-reflex-like mechanisms to a number of hyperperfusion states [5][6][7]. Sensory axons are largely unmy elinated C Fibers which form a plexus within the adventitia.…”
Section: Introductionmentioning
confidence: 99%